Literacy assessment and instructional strategies : connecting to the common core - Grant, Kathy B; Golden, Sandra; Wilson, Nance S (Thousand Oaks, California : Sage Publications, 2015)
This practical book prepares teachers to conduct reading and writing assessments and develop appropriate corrective literacy strategies for grades K-5 students. It connects the Common Core Literacy Learning Standards to thse effective strategies and creative activities, and included authentic literacy assessmemnts and formal evaluations to support the teaching of reading in the elementary classroom, divided into chapters for kindergarten, primary and intermediate grades.
Includes bibliographical references and index.
Keywords: Language arts -- Ability testing -- United States; Reading -- Ability testing -- United States; Literacy -- Evaluation; Language arts -- Standards -- United States; Educational tests and measurements -- United States